Management control systems for university spin-off (Costos y Gestión, 2024)
The entrepreneurial mission in universities has led to a paradigm shift, previously thought of as “research at the university”. Now, this research must necessarily be associated with its transfer to the environment, contributing to the development of the territory. This transfer can take place in different ways. This research is focused on analyzing university spinoffs, which are mostly included within the Technology Based Companies (TBC), whose differentiating feature of competitiveness is the intensive use of scientific and technical knowledge. The objective is to identify the phases or stages of university TBEs, management needs and management control systems for their better performance. The research is descriptive, with a qualitative methodology, addressing two cases of university spin-offs arising from an Argentinean public management entity. The results show that, in the University selected as a case study, the presence of different factors recognized by the literature as drivers of technology transfer is evident, while in the two spin-offs analyzed, the stages within the life cycle proposed for EBTs by reference authors and the management control systems used for their planning and control were identified.
Keywords: management accounting; information systems; technology-based companies